DEVELOPMENT OF CHARACTER EDUCATION MODELS - Ike Nilawati Rohaenah; Sahudi; Aan Hasanah (IJGIE (International Journal of Graduate of Islamic Education), 2021)
The research method used was qualitative. The research site of Mutiara Bangsa Health Vocational School, Purwakarta, West Java. The number of respondents was 38 grade X students. The results of the study were as follows: 1) The character education curriculum at Mutiara Bangsa Health Vocational School was arranged perfectly. 70% of the subject matter is in the form of practice and 30% is theory. 2). The character education model has been used by using the "Qishah or Story Model, Uswah or Exemplary Model, Habitual Model, Teaching Model, Priority Determination Model. Practical Model Priority Habitual Reflection Model". 3) Character education program. has been done . The achievement is at a good stage. 4) The implementation of the character education model has been carried out well. 5) Facing obstacles and strengthening the implementation of the character education model are carried out mutually and continuously work hand in hand to overcome obstacles. but only achieved good not yet perfect 6) The results of the implementation of the character education model have been good. Weight of Perfect Points A = 85-100. Good 76-84. Enough 66- 75. Less 50-65. The results of character education grow attitudes: 1). Religious. 2) Honest 3) Tolerance 4) Discipline 5) Hard work 6) Creative, 7) Independent, 8) Democratic 9) Curiosity Keywords: Model Development, Character Education Curriculum, Model. Program, Implementation, Overcoming obstacles, Result of implementation.